Landscape management innovations in Ghana by CGIAR and IWMI - International Water Management Institute (International Water Management Institute, 2023)
Most social-ecological landscapes are under threat due to poor resource management compounded by the impacts of climate change. The international Water Management Institute (IWMI) employs an inclusive landscape management approach for scaling innovations to transform food systems in degraded landscapes. This video highlights such innovations being deployed in Ghana through the #ONECGIAR Initiative on Transforming Food Systems in West and Central Africa (TAFS-WCA).